A Desirability of Outcome Ranking Analysis of a Randomized Clinical Trial Comparing Seven Versus Fourteen Days of Antibiotics for Uncomplicated Gram-Negative Bloodstream Infection. (9th April 2022) - Howard-Anderson, Jessica; Dai, Weixiao; Yahav, Dafna; Hamasaki, Toshimitsu; Turjeman, Adi; Koppel, Fidi; Franceschini, Erica; Hill, Carol; Sund, Zoë; Chambers, Henry F; Fowler, Vance G; Boucher, Helen W; et al.
Abstract: Background: Although a short course (7 days) of antibiotics has been demonstrated to be noninferior to a conventional course (14 days) in terms of mortality and infectious complications for patients with a Gram-negative bacterial bloodstream infection (GNB), it is unknown whether a shorter treatment duration can provide a better overall clinical outcome. Methods: We applied a bloodstream infection-specific desirability of outcome ranking (DOOR) analysis to the results of a previously completed, randomized controlled trial comparing short versus conventional course antibiotic therapy for hospitalized patients with uncomplicated GNB. We determined the probability that a randomly selected participant in the short course group would have a more desirable overall outcome than a participant in the conventional duration group. We performed (1) partial credit analyses allowing for calculated and variable weighting of DOOR ranks and (2) subgroup analyses to elucidate which patients may benefit the most from short durations of therapy. Results: For the 604 patients included in the original study (306 short course, 298 conventional course), the probability of having a more desirable outcome with a short course of antibiotics compared with a conventional course was 51.1% (95% confidence interval, 46.7% to 55.4%), indicating no significant difference. Partial credit analyses indicated that the DOOR results were similar across different patient preferences. Prespecified subgroup analyses using DOOR did not reveal significant differences between short and conventional courses of therapy. Conclusions: Both short and conventional durations of antibiotic therapy provide comparable clinical outcomes when using DOOR to consider benefits and risks of treatment options for GNB. Abstract : We retrospectively applied a desirability of outcome ranking analysis to a randomized controlled trial comparing short versus conventional durations of antibiotics for Gram-negative bacteremia. A short duration of antibiotics provided similar desirability of clinical outcomes as a conventional duration.